The effect of a potentially tamper-resistant oxycodone formulation on opioid use and harm: main findings of the National Opioid Medications Abuse Deterrence (NOMAD) study. (February 2018) - Larance, Briony; Dobbins, Timothy; Peacock, Amy; Ali, Robert; Bruno, Raimondo; Lintzeris, Nicholas; Farrell, Michael; Degenhardt, Louisa
Summary: Background: Escalation of pharmaceutical opioid use and harm in North America is well-documented, with similar issues emerging in Australia. One response is the development of tamper-resistant formulations of opioids. A potentially tamper-resistant formulation of controlled-release oxycodone was introduced in Australia in April, 2014, rapidly replacing the non-tamper-resistant formulation. Our study is the most systematic and comprehensive examination of the impact of a new opioid formulation to date, assessing the effect of tamper-resistant formulation of controlled-release oxycodone on population-level opioid use and opioid-related harm (ie, overdose, help-seeking, and treatment-seeking); and opioid use, tampering, and preference for the tamper-resistant formulation of controlled-release oxycodone compared with other drugs or formulations among sentinel populations likely to tamper with pharmaceutical opioids. Methods: We conducted interrupted time-series analyses of opioid sales data and multiple routinely collected health datasets, followed up a cohort of people who tamper with pharmaceutical opioids before and after the introduction of the tamper-resistant formulation of controlled-release oxycodone, and analysed annual surveys of people who inject drugs. Data were collected from several Australian states: New South Wales, South Australia, and Tasmania. Meta-analyses (weighted Z tests) were conducted to synthesise across data sources providing evidence for a given indicator. Findings: At the population level, we found reduced sales of higher strengths of controlled-release oxycodone and increased sales of other oxycodone formulations. No significant effect was observed among population-level indicators of opioid overdose, or help or treatment-seeking. Mortality data were not available for inclusion at the time of our study. Meta-analyses across sentinel populations (ie, prospective cohort, surveys of people who inject drugs, and clients of supervised injecting facilities or needle and syringe programmes) indicated reduced controlled-release oxycodone use via tampering (mainly injection), with no evidence of switching to heroin or other drug use. Interpretation: This formulation of controlled-release oxycodone reduced tampering with pharmaceutical opioids among people who inject drugs, but did not affect population-level opioid use or harm. Funding: Mundipharma Australia, the Australian Government, and the National Health and Medical Research Council.